2023
DOI: 10.3390/cancers15092472
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Changes Energy Metabolism and Growth Rate in Non-Small Cell Lung Cancer Cells

Abstract: Hypoxia occurs in 80% of non-small cell lung carcinoma (NSCLC) cases, leading to treatment resistance. Hypoxia’s effects on NSCLC energetics are not well-characterized. We evaluated changes in glucose uptake and lactate production in two NSCLC cell lines under hypoxia in conjunction with growth rate and cell cycle phase distribution. The cell lines A549 (p53 wt) and H358 (p53 null) were incubated under hypoxia (0.1% and 1% O2) or normoxia (20% O2). Glucose and lactate concentrations in supernatants were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Copyright 2021, Frontiers Media SA, Angiogenesis Reproduced with permission [33] . Copyright 2022, Multidisciplinary Digital Publishing Institute (MDPI), Metabolism Reproduced with permission [37] . Copyright 2023, Multidisciplinary Digital Publishing Institute (MDPI), Immunoresponse Reproduced with permission [42] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2021, Frontiers Media SA, Angiogenesis Reproduced with permission [33] . Copyright 2022, Multidisciplinary Digital Publishing Institute (MDPI), Metabolism Reproduced with permission [37] . Copyright 2023, Multidisciplinary Digital Publishing Institute (MDPI), Immunoresponse Reproduced with permission [42] .…”
Section: Discussionmentioning
confidence: 99%
“…[33] Copyright 2022, Multidisciplinary Digital Publishing Institute (MDPI), Metabolism Reproduced with permission. [37] Copyright 2023, Multidisciplinary Digital Publishing Institute (MDPI), Immunoresponse Reproduced with permission. [42] Copyright 2016, Frontiers Media SA, Cell Death Reproduced with permission.…”
Section: Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 Tumour cells are predisposed to produce ATP through glycolysis at both hypoxia and normoxia to promote tumour cell growth. 38 Hexokinases are the rate‐limiting enzymes in promoting glycolysism, and it has been upregulated in cancers by many factors such as activated ERBB2, RAS and AKT, as well as loss of p53. 39 HK2, a key member of the HK family, catalyzes the first committed step in glucose metabolism by phosphorylating glucose, and it is specifically expressed in many foetal tissues and cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ability to block both PC and glutaminase by MSeA and selenite, but not by SeM, correlated well with their ability to inhibit cell proliferation and to induce ROS production. These effects of MSeA and selenite on anaplerosis led to reduced Krebs cycle activity, which in turn attenuated de novo synthesis of nucleotides and lipids, all required for supporting cell proliferation [ 93 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. We have previously shown that PC is activated in vivo in NSCLC patient tumors [ 61 ], and that both PC and glutaminolysis are important for supporting lung cancer cell proliferation [ 91 ] .…”
Section: Discussionmentioning
confidence: 99%